Urban Expansion, Green Infrastructure Decline, and Windstorm Vulnerability in Bauchi: Mapping, Matrix, and Correlation Analyses - Abdulkadir Aliyu; Luka Fitto Buba; Kafi, Kamil Muhammad; Rasheed Osuolale Oladosu; Mohammed Abdulkadir; Mubina Auwal Muallim (Urban Planning and Construction, 2026)
Rapid urbanization across the Global South has led to a substantial decline in urban vegetation, increasing the exposure of cities to climate-related hazards. In Sub-Saharan Africa, this trend has heightened vulnerability to extreme weather events, particularly windstorms. Bauchi, a fast-growing city in Nigeria, has recently experienced severe and recurring windstorm damage, raising concerns about the role of urban expansion in shaping disaster risk. This study investigates the relationship between urban growth and windstorm vulnerability using a multi-method quantitative approach. Spatio-temporal analysis of land use/land cover (LULC), an urban vulnerability matrix, and linear correlation analysis were integrated to examine changes in urban green infrastructure (UGI) and expansion dynamics over 20 years (2004–2024). The findings indicate rapid urban expansion accompanied by a significant transformation of vegetation structure. Dense and moderately dense vegetation declined by 59% and 26%, respectively, while sparse vegetation increased by 51%, expanding from 122 km2 to 250 km2. This shift reflects a progressive degradation of UGI, resulting in the loss of natural wind-buffering capacity and increased exposure of the built environment to windstorm impacts. The study proposes a conceptual framework that repositions UGI as a strategic tool for enhancing urban resilience. The findings underscore the urgent need to embed UGI strategies into revised urban master plans to reduce risk, protect infrastructure, and support a more resilient and sustainable urban future for Bauchi.